Human Capital Strategy Implementation for Start-up Business Over Islamic Boarding Schools (Pesantren) Noor Halal Minimarket - Herriyanto Kurniawan; Tantri Yanuar Rahmat Syah; Rhian Indradewa; Diana Fajarwati (Journal of Multidisciplinary Academic, 2020)
The rapid growth of the retail industry affects the mindset of the people so that people change their consumption style by choosing to shop at minimarkets, supermarkets, or hypermarkets due to more comfortable compared by traditional stores. The growth index value of minimarkets in Indonesia is based on data released by APRINDO (Indonesian Retail Employers Association) in January 2019 is increased 15%. Thus, the magnitude of potential retail business opportunities over Noor Halal Minimarket was established and focuses on Islamic Boarding Schools (Pesantren) area which is have a new business model and cannot explored by the national minimarket network. Based on the calculation’s analysis and business strategy analysis, Noor Halal Minimarket has a profitable business opportunity. Noor Halal Minimarket develops business starting in 2020 by opening 10 minimarkets in the period of 1 to 2 years, increasing to a total of 22 minimarkets in the period 3 to 4 years and increasing to a total of 36 minimarkets in the 5th year period all of which are located in Bogor Regency, West Java, considering that Bogor Regency has the highest number of pesantren and students in Indonesia. Noor Halal Minimarket uses the concept of competency-based human capital management to achieve company goals so as to provide optimal service to customers. The key to the company's success refers to human capital management in developing business is supported by competent employees who have high work motivation to provide excellent service to customers.